"Bad Things Happened": How Children of the Digital Age Make Sense of Violent Current Events. Issue 2 (4th March 2019) - Zakai, Sivan
Abstract: Digital technologies collapse distance and accelerate the speed at which information travels. This has made it easier for children to encounter violent clashes from across the globe. Thus, the digital era has raised new questions for educators about how to teach current events in an increasingly globalized world. When children have easy access to information, how do they make sense of what they see and hear? When world events take a violent turn, what cognitive and emotional sense-making strategies do children employ? And, in light of children's developing thoughts and feelings about global affairs, what role should educators play in helping children make sense of violent current events? This research explores these questions by examining one particular case of children's understanding of violent current events. Through interviews and storytelling exercises it investigates how a group of Jewish children in the United States attempted to make sense of the 2014 war between Israel and Hamas, interrogating the cognitive and emotional sense-making strategies that the children employed. In doing so it highlights the opportunities and challenges of current events education at a time of unprecedented global connectivity.